(untitled) (Research Journal of Padmakanya Multiple Campus, 2023)
The article is based on the issues of violence against women (VAW) by their husbands. The experience of physical violence faced by women from their husband in Nepal is the main focus of this article. Violent behaviors like physical attacks or harm done by men against women have been unfortunate events in individuals. The article shows the status of Nepal in the world in the context of violence. The objectives of the article are to identify the situation of violence against women by age, level of education, caste/ ethnicity and occupation of the women. The data for this article was collected by cross-sectional survey and the study was quantitative descriptive study. The prevalence of all forms of VAW by husband was common among women aged 15-49. Even physical violence (22.8%) was higher than emotional (12.3%) and sexual (7%) violence. Physical violence is pervasive in any status of the women; in such a situation the government must focus its programs to eliminate any type of violence against women.